USABILITY APLIKASI ANDROID HONDA e-Care DENGAN USE QUESTIONNAIRE DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Kudiantoro Widianto (Jurnal Poli-Teknologi, 2021)
Honda Pondok Pinang, which is located on Jl. Ciputat Raya No.80 Pondok Pinang, South Jakarta, in customer service using an android application called HONDA e-Care. HONDA e-Care is very helpful in making it easier for consumers to access Honda service services. With the Honda e-Care application, customers online carry out ordering services, traffic notification of periodic maintenance schedules, and look on digital to find dealers with the closest distance from the location. But consumers often also get security such as when making an order service but ordering service that is not showing up. Research on the quality of the Honda e-Care application has yet to be carried out. This study aims to measure the usability of the HONDA e-Care android application and provide suggestions for developing the HONDA e-Care application in the future. Based on the gap analysis, it was found that in general the use of the HONDA e-Care android application on the Honda Pondok Pinang was not satisfied with the quality of the current applications. With the IPA analysis, the priority scale for improving the quality of the HONDA e-Care android application is mapped where quadrant I is the priority scale based on the user's perspective, namely: The HONDA e-Care android application is easy to operate; The search facility on the HONDA e-Care android application is functioning properly; The HONDA e-Care android application is easy to download; Image symbols on the HONDA e-Care android application easy implementation; and Access product information on the HONDA e-Care android application is easy to obtain. Managers must increase the four items in order to meet user expectations.